An empirical analysis on the factors influence employee turnover intention in banking sector: Evidence from Penang, Malaysia / Arvindraj Naidu Nagarajah and Jaya Kumar Shanmugam - Nagarajah, Arvindraj Naidu; Shanmugam, Jaya Kumar (UiTM Cawangan Negeri Sembilan, 2022)
This research is about to explore factors that impact employee's turnover intention in banking sector in Penang. High employee turnover rate may not just affect the corporation's goals, it leads to negative effect. There are a few factors anticipate impacting the employee's turnover intention which are distributive justice, compensation, job stress and job satisfaction. The underpinning theory for this study determines on two factor theory (Motivator-Hygiene). A sum of 150 bank employees from various banks in Penang, Malaysia were chosen, and questionnaires were disseminated to them. The outcomes indicate that there is a positive connection between all factors and employee's turnover intention. All variables have an impact towards employee's turnover intention. This investigation helps the bank management to recognize the potential factors that impact their staff to resign from the present place of employment. A few proposals and recommendations for further research are also consider toward the end of this research.